MORPHOLOGICAL STRUCTURAL FEATURES HEARTS IN MINERAL METABOLISM DISORDERS - Khidirova G. O. (Journals Park Publishing, 2026)
Disturbances in mineral metabolism (calcium, phosphorus, magnesium, potassium, and sodium) play a key role in the formation of structural and functional changes in the myocardium. Deficiency or excess of certain macro- and microelements leads to disruption of cardiomyocyte ion homeostasis, imbalance in calcium channel activity, and alterations in depolarization and repolarization processes. This is accompanied by morphological changes in cardiac tissue, including cardiomyocyte dystrophy and necrosis, interstitial edema, stromal sclerosis, and myocardial remodeling. Prolonged mineral metabolism disorders contribute to myocardial hypertrophy, fibrosis, microcirculatory disturbances, and accelerated development of heart failure. Of particular importance are changes in calcium-phosphorus metabolism, which are closely associated with endocrine regulation (parathyroid hormones, vitamin D), as well as potassium-magnesium imbalance, which directly affects the contractile function of the heart. Studying the morphological mechanisms of cardiac structural damage in mineral imbalance provides prospects for pathogenetically based prevention and therapy of cardiovascular diseases.
Keywords: Mineral metabolism, calcium, phosphorus, potassium, magnesium, myocardium, cardiomyocytes, morphological changes, dystrophy, necrosis, hypertrophy, fibrosis, heart failure, myocardial remodeling, microcirculation, vitamin D, parathyroid hormone.